Biochemical and serological characterization of Mycoplasma from bovine clinical mastitis in southwest and northern Nigeria (2010)
The primary objective of this study was to isolate and characterize the mycoplasma species present in clinical cases of mastitic cows in Southwest and Northern Nigeria and to determine the prevalence of mycoplasma mastitis in dairy cows. Two hundred milk samples were collected from cases of clinical mastitic cows in Ibadan,Ilorin and Kaduna. Mycoplasma was isolated from thirty-two milk samples, these milk samples were analysed bacteriologically and mycoplasmologically. The recovered pathogens were characterized biochemically using various tests. The mycoplasma species were also serologically identified by growth inhibition tests (GIT) using antisera produced in Rabbit against the mycoplasma strains. The Mycoplasma species identified from this include: 13 isolates of Mycoplasma bovis; 8 isolates of Mycoplasma mycoides sub sp. mycoides; 7 isolates of Mycoplasma capricolum and 4 isolates of Mycoplasma arginini. Other pathogens isolated include: Streptococcus species, Staphylococcus aureus, coagulase negative Staphylococcus, Escherichia coli, Klebsiella pneumoniae and Pseudomonsa aeruginosa. Based on the public health and economic significance of mycoplasma spp identified in this study, couple with the fact that consumption of such unpasteurized milk is a frequent occurrence among the rural dwellers which could result in milk borne zoonoses, it is suggested that fresh milk should be properly pasteurized before consumption by humans. Key words : Bovine; Mastitis; Biochemical;Serological;Mycoplasma; Nigeria.